PENGEMBANGAN POTENSI SUMBER DAYA MANUSIA YANG UNGGUL DAN KREATIF MELALUI BIDANG PENDIDIKAN DASAR - LEILY CHOIRUROHMAN; ADHIPUTRO PANGARSO WICAKSONO (KRIDA CENDEKIA, 2022)
Education is one of the main influences of changes in social attitudes that can change the pattern of human thought. Basic education is important in the formation of human potential as stated in the national education goals of Law no. 20 of 2003 Article 3. This socialization is carried out to realize contributions to the community in facing the development of science and technology by improving the quality of human resources through the field of basic education. So with the existence of quality human resources, the community is easier to deal with the times. In children’s teaching learning process is also constrained by boring teaching and learning activities, so innovation and creativity are needed in a learning process.